Pembiayaan Pendidikan Anak Yatim Piatu Sebagai Dampak Sekunder Pandemi Covid-19 di Indonesia Melalui Zakat - Wijaya, Buana Handa; Hanifuddin, Iza (Invest Journal of Sharia & Economic Law, 2021)
The Covid-19 pandemic has a secondary impact: the emergence of orphaned children due to losing one or both caregivers. Primary data of the children are used to implement child rights protection. The program must be run on target according to the characteristics and needs of children's rights. The research method used in this research is library research. These research variables include the impact of the Covid-19 pandemic in Indonesia on children, the role of zakat in supporting the education of children who have lost one or both caregivers, and legal certainty in supporting children's education during the Covid-19 pandemic in Indonesia. A single agency cannot solve educational problems for these children during the Covid-19 pandemic. Program cooperation from various parties such as multilateral organizations, national and local governments, non-governmental and faith-based organizations, voluntary organizations, and donors can overcome the secondary impact of the Covid-19 pandemic on these children. BAZNAS, as a national zakat management institution in Indonesia, has distributed zakat funds in supporting the field of education during the Covid-19 pandemic (2020-2021). However, no programs specifically lead to educational assistance to orphaned children due to the loss of one or both caregivers (parents or grandparents) during the Covid-19 pandemic. The implementation of educational services for vulnerable children experiencing school dropouts during the Covid-19 pandemic should be accompanied by a clear legal umbrella in ensuring the sustainability of education